Réponses

2013-11-13T21:12:39+01:00
Bonjour,

En comparant les deux équations, nous avons : 

\dfrac{3}{8}x-\dfrac{31}{8}=\dfrac{4}{5}x+\dfrac{2}{5}\\\\\dfrac{3x-31}{8}=\dfrac{4x+2}{5}\\\\5(3x-31)=8(4x+2)\\\\15x-155=32x+16\\\\15x-32x=16+155\\\\-17x=171\\\\x=-\dfrac{171}{17}

Remplaçons x par cette valeur dans la première équation.

y=\dfrac{3}{8}\times(-\dfrac{171}{17})-\dfrac{31}{8}\\\\y=-\dfrac{513}{136}-\dfrac{527}{136}\\\\y=-\dfrac{1040}{136}\\\\y=-\dfrac{130}{17}

Donc  S=\{(-\dfrac{171}{17};-\dfrac{130}{17})\}